1978
DOI: 10.1002/cne.901780302
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic projections to S‐I in macaque monkey

Abstract: The organization of thalamic input to functionally characterized zones in primary somatosensory cerebral cortex (S-I) of macaque monkeys (Macaca mulatta) was investigated using the method of labelling by retrograde transport of horseradish peroxidase (HRP). It was found that the cell columns positioned at the posterior margin of the band of cortex representing a given body region receive thalamic input from a posterior level of the ventroposterior thalamic nucleus (VP), and that cell columns at successively mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1979
1979
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…The cortical connections of area 3a are distinct from other somatosensory areas in that area 3a receives its densest input from cortical areas associated with the motor system, including the primary (M1), supplementary (SMA), and premotor (PM) areas. Area 3a is also densely interconnected with areas in the posterior parietal cortex (Huffman and Krubitzer, 2001), which is associated with complex behaviors such as goal-directed reaching (Ferraina and Bianchi, 1994;Snyder et al, 1997Snyder et al, , 1998Andersen et al, 1997; for reviews, see Mountcastle et al, 1984;Andersen et al, 2000) Although the thalamic connections of other anterior parietal fields have been well investigated (Whitsel et al, 1978;Jones et al, 1979;Nelson and Kaas, 1981;Cusick et al, 1985;Mayner and Kaas, 1986;Cusick and Gould, 1990;Krubitzer and Kaas, 1992; for reviews, see Jones, 1985;Kaas and Pons, 1988), only a few previous studies in monkeys have examined the thalamo-cortical connections of area 3a. Furthermore, most studies define area 3a by using architectonic criteria alone, which can be problematic (Jones and Porter, 1980).…”
mentioning
confidence: 97%
“…The cortical connections of area 3a are distinct from other somatosensory areas in that area 3a receives its densest input from cortical areas associated with the motor system, including the primary (M1), supplementary (SMA), and premotor (PM) areas. Area 3a is also densely interconnected with areas in the posterior parietal cortex (Huffman and Krubitzer, 2001), which is associated with complex behaviors such as goal-directed reaching (Ferraina and Bianchi, 1994;Snyder et al, 1997Snyder et al, , 1998Andersen et al, 1997; for reviews, see Mountcastle et al, 1984;Andersen et al, 2000) Although the thalamic connections of other anterior parietal fields have been well investigated (Whitsel et al, 1978;Jones et al, 1979;Nelson and Kaas, 1981;Cusick et al, 1985;Mayner and Kaas, 1986;Cusick and Gould, 1990;Krubitzer and Kaas, 1992; for reviews, see Jones, 1985;Kaas and Pons, 1988), only a few previous studies in monkeys have examined the thalamo-cortical connections of area 3a. Furthermore, most studies define area 3a by using architectonic criteria alone, which can be problematic (Jones and Porter, 1980).…”
mentioning
confidence: 97%
“…According to recent physiological stud ies [44,71] the VBC can be functionally di vided into centrally located 'core' and pe ripherally located 'shell' zones. In ma caque, the core zone contains neurons ac tivated primarily by cutaneous tactile re ceptors [44], receives dense projection from the dorsal column nuclei [10], and contains clusters of spinothalamic pre terminals after cord hemisection [II].…”
Section: Functional Significance O F Vimmentioning
confidence: 99%
“…The 'intermediate zone' also receives input from the vestibular complex in both cat [7,41,63] Several investigations have indicated that the rostral 'shelf zone (i.e., Vim) pro jects to area 3a [24,30,33,66,71]. Physio logical studies have indicated that the cor tical area 10 which Vim projects (i.e., 3a) contains cells which are activated by slow ly adapting muscle and joint receptor in put [16,59,62,71]. Although area 3a has classically been described as the most ros tral part of S-I [71], recent evidence by Jones et al [29] includes the portion of 3a to which the intermediate thalamic zone (VPL0/V1C ) projects as part of the motor cortex: area 4.…”
Section: Functional Significance O F Vimmentioning
confidence: 99%
See 2 more Smart Citations